Oral gargle-tumor biopsy human papillomavirus (HPV) agreement and associated factors among oropharyngeal squamous cell carcinoma (OPSCC) cases. (May 2019) - Martin-Gomez, Laura; Fulp, William J.; Schell, Michael J.; Sirak, Bradley; Abrahamsen, Martha; Isaacs-Soriano, Kimberly A.; Lorincz, Attila; Wenig, Bruce; Chung, Christine H.; Caudell, Jimmy J.; Giuliano, Anna R.
Highlights: Assessed HPV status agreement between oral gargle vs. tumor biopsy among OPSCC. 83% of oral gargle and 93% of tumor biopsy specimens were HPV positive. 73.7% oral-tumor agreement for oncogenic and HPV 16. Oral-tumor agreement was higher among older and cases with late disease. Abstract: Objective: Assess oral gargle-tumor human papillomavirus (HPV) agreement among oropharyngeal squamous cell carcinoma (OPSCC) cases by several disease characteristics. Materials and methods: 171 treatment naïve OPSCC were enrolled 2014–2017. Tumors were categorized as early or late disease with early disease defined as T1-2 with no nodal involvement or at most a single ipsilateral positive node <3 cm. Oral gargle samples were obtained via a 30-second rinse and gargle. The RHA Kit HPV SP10 -LiPA25 was utilized for HPV genotyping of tumor (FFPE) and oral gargle specimens. Sensitivity, specificity, positive and negative predictive value, percent agreement, and 95% exact binomial confidence intervals were estimated. Multivariable logistic regression models were fit to predict agreement. Results: 83.0% and 93.0% of oral gargle and tumor specimens were HPV positive. Oral gargle-tumor agreement for any oncogenic HPV type and HPV 16 was 73.7%. High oncogenic HPV oral gargle-tumor agreement was observed for late disease presentation, p16 positive cases, and tumors at the tonsils (74.5–80.8%). Similar trends were observed for HPV 16. Agreement for any oncogenic HPV and HPV 16 was significantly higher for late vs. early disease (77.9% vs 57.1%, p = 0.01). Oral gargle-tumor oncogenic HPV and HPV 16 agreement was independently associated with age ≥50 years and late disease presentation. Conclusion: Overall, oral-tumor HPV agreement among OPSCC was relatively high. However, oral-tumor HPV agreement was significantly lower among younger cases and those diagnosed with earlier disease. Additional biomarkers are needed to improve oral HPV test characteristics to identify OPSCC early.